Effect of Geranylgeraniol and Green Tea Polyphenols on High-fat-diet-induced Bone Deterioration in Male B6 Mice (P06-025-19) - Shen, Chwan-Li (Curr Dev Nutr, 2019)
OBJECTIVES: To investigate the combined effects of geranylgeraniol (GG, a 20-carbon isoprenoid found in fruits, vegetables, and grains) and green tea polyphenols (GTP, extracted from green tea) on high-fat-diet (HFD) induced bone deterioration in obese male mice. Our previous studies demonstrated that GG or GTP, when supplemented separately, was beneficial to the bone health of obese animals. Therefore, we hypothesized that GG combined with GTP would improve bone structure of obese mice fed a HFD. METHODS: Forty-eight male C57BL/6 J mice were assigned to 4 groups (n = 12/group) in a 2 (no GG vs. GG) × 2 (no GTP vs. GTP) factorial design: HFD, HFD + GG (400 mg GG/kg diet), HFD + GTP [0.5% (w/v) in drinking water], and HFD + GG + GTP. Animals were fed the respective diet ad libitum for 14 weeks. RESULTS: GTP supplementation, not GG, resulted in lower final body weight and greater fasting serum insulin concentrations. Supplementation of GG or GTP (separate, but not together) lowered blood glucose concentrations at 120 min. A decreased area under the curve of glucose tolerance tests and insulin tolerance test in the HFD + GG + GTP group was observed suggesting improved glucose clearance and insulin sensitivity, but no interaction was found between GG and GTP. Neither GG nor GTP affected serum concentrations of insulin or procollagen type I intact N-terminal (a bone formation marker). There was an interaction effect for serum concentrations of collagen type 1 cross-linked C-telopeptide (CTX, a bone resorption marker), resulting in HFD + GG + GTP being the lowest. Neither GG nor GTP supplementation affected the total area, bone area, and cortical thickness at the femur midshaft or the bone volume/total volume at the lumbar vertebrae. GG supplementation increased trabecular number and decreased trabecular separation at the lumbar vertebrae. GTP supplementation increased trabecular thickness at lumbar vertebrae. HFD + GG produced the greatest connectivity density and the lowest structure model index. CONCLUSIONS: This study suggests a beneficial role of supplementing GG with GTP in bone health of obese animals. FUNDING SOURCES: The study was supported by American River Nutrition to CLS and USDA ARS Project no. 3062-51,000-053-00D.